Pengembangan EcoHYPTOR (Economical Hydraulic Pascal Demonstrator) sebagai Alat Peraga Pembelajaran Fisika Materi Fluida - Rahma Tiara Lestari; Asep Irvan Irvani; Resti Warliani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The abstract conceptual nature of static fluid material, especially Pascal;s Law, often becomes a learning obstacle for senior high school (SMA) students. This condition is exacerbated by limited laboratory facilities and the minimal use of concrete media in schools. This study aims to produce an innovative hydraulic demonstration tool called EcoHYPTOR (Economical Hydraulic Pascal Demonstrator) that meets the criteria of being valid, practical, and feasible as a high school physics learning medium. The method used is Research and Development (R&D) with the ADDIE development model, which is limited to the small-scale implementation stage (limited trials). Data collection was carried out through interview guidelines, media expert validation sheets, and user response questionnaires. The result of the media expert assessment showed that the validity level of EcoHYPTOR reached an average of 89% (Very Valid), with a perfect achievement of 100% in the aspect of clarity, safety and efficiency. Furthermore, limited user trials resulted in a response percentage of 92% (Very Good). It can be concluded that the EcoHYPTOR teaching aid is highly feasible, safe, and practical to use as an alternative learning medium to concretely visualize the principles of Pascal’s Law, especially in schools with limited laboratory facilities.